EVALUATION OF EXTERNAL TRADE COOPERATION AMONG RUSSIA, KAZAKHSTAN, AND BELARUS THROUGH SHIFT COMPONENTS METHOD - Svetlana N. Bludova (Вестник Северо-Кавказского федерального университета)
The item contains an analysis of the external trade among Russia, Belarus, and Kazakhstan employing the shift components method. There is also an evaluation of the impact that the integration, sectoral, and country components have of the outcomes of the export-import activities among the countries.